Recuperación y mejora técnica del módulo didáctico de sistema de frenos del laboratorio de mecánica automotriz de la Universidad Antonio Nariño Sede Neiva. (2020)
This degree work consisted of recovering the technical functions of various elements of the didactic module of the brake system that existed in the UAN NEIVA automotive mechanics laboratory, identifying the damage of some equipment and expanding the possibilities of carrying out more activities within from the area of automobile mechanics and fluid mechanics, since the brake system includes equipment that works in these subjects. The module was in a NON-FUNCTIONAL condition since it lacked maintenance; in a first inspection its structure is corroded and with several missing parts; likewise it is found that the structure has spaces that are not yet usable; module security is precarious because there are mobile elements and there are no security guards that allow proper work. The recovery of this type of modules was necessary because as a fixed asset of the university it requires its constant manipulation so that its not only commercial but academic value is not depreciated. Currently the institution is in the process of institutional accreditation as well as in the renewal of its qualified registers such as that of Mechanical Engineering and Electromechanical Engineering. For this reason, this type of work is necessary as a recovery strategy for the laboratory equipment available to the University and as a strengthening of the program content (syllabus) of the Engineering programs. This work was developed in several methodological phases. The first one under the first objective, based on Bloom's taxonomy